THE PRINCIPLES OF ENVIRONMENTAL MANAGEMENT SYSTEM IMPLEMENTATION AT FILLING STATIONS - Радомська, М. (Proceedings of National Aviation University, 2012)
The article is devoted to the analysis of means environmental safety enhancement at filling stations of common use. One of the most important directions of industrial enterprises environmental problems solution is development of the specialized complexes of nature protection activities in the form of EMS. Advantages of EMS implementation at enterprises were considered in the article. Principles and stages of EMS formation and introduction were developed for filling stations. Based on this the recommendations on implementation of all procedures and works aimed at formation and introduction of EMS at filling stations were given. The priority components and sources of filling stations negative environmental impacts were selected and the directions of filling stations ecologization were indicated